CLINICAL, PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF ACUTE BRONCHIOLITIS IN CHILDREN UNDER 2 YEARS AT HAU GIANG OBSTETRICS AND PEDIATRICS HOSPITAL, 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical and paraclinical features and treatment outcomes of acute bronchiolitis in children under 2 years treated at Hau Giang Obstetrics and Pediatrics Hospital in 2024.Methods: We conducted an observational, non‑interventional study using a structured case record form. Data included demographics, clinical presentation, laboratory tests, chest radiography and in‑hospital outcomes. Data were coded and analyzed with descriptive statistics; Chi‑square tests assessed associations (p < 0.05). Ethical approval was obtained from Vo Truong Toan University and Hau Giang Obstetrics and Pediatrics Hospital.Results: A total of 64 children were included (mean age 8.5 ± 6.6 months); 51.6% were boys and 78.1% lived in rural areas. Cesarean delivery accounted for 7.8%; low birth weight (< 2500 g) was 3.1%. Most children had leukocytosis > 10 × 103/mm3 (95.3%). Platelets > 400 × 10⁶/mm³ accounted for 40.6%. Length of stay ≥ 7 days was more frequent among malnourished children (72.3%) than those with normal nutrition (21.7%).Conclusion: Acute bronchiolitis predominantly affected infants under 12 months. Leukocytosis was common and poor nutritional status was associated with prolonged hospitalization. Findings provide local evidence to optimize clinical management and identify children at risk for longer stays.
Keywords: Acute bronchiolitis, infants, clinical features, laboratory findings, treatment outcomes.